Eksplorasi Perancangan Rumah Tinggal Sederhana di Daerah Permukiman Padat Kampung Kota dalam Menjawab Isu Efisiensi Energi (Studi Kasus pada Lahan dengan Luas 40m2) - Anjar Primasetra (PLANNERS INSIGHT : URBAN AND REGIONAL PLANNING JOURNAL, 2019)
Energy efficiency in homes, especially in densely populated urban dwellings, is an important issue. This paper aims to provide a house design proposal to solve the problem of densely populated urban settlements, which is carried out by designing exploration. The design method used in this study is an ecological architecture approach, which is adapted to the context of tropical climate, limited land, and the assumption of small family lifestyles with middle to lower economic conditions. The case study taken is a house on an area of 40 m2 with the hope that the size of this land represents a limited area of land in dense settlements in urban villages.